13.2k views
2 votes
-6x+5-4(x-1)=-4x-(5x-3)+4

User MDStephens
by
6.0k points

1 Answer

1 vote
Hello there!

-6x + 5 - 4(x - 1) = -4x - (5x - 3) + 4

We need to use the distributive form

-6x + 5 + (-4)(x) + (-4)(-1) = -4x - 5x + 3 + 4

-6x + 5 - 4x + 4 = -4x - 5x + 3 + 4

-10x + 9 = -9x + 7

Now we can subtract 9 from both sides

-10x + 9 - 9 = -9x + 7 - 9

-10x = -9x - 2

Add 9x to both sides

-10x + 9x = -9x + 9x - 2

-x = -2

We cannot leave it with a negative sign, divide both sides by -1

-x/-1 = -2/-1

x = 2

I hope the steps are clear to understand. If you have any misunderstanding feel free to let me know.

As always, I am here to help!
User Delbertooo
by
6.0k points